MicroRNA and metabolomics signatures for adrenomyeloneuropathy disease severity. Issue 6 (22nd August 2022) - Turk, Bela Rui; Poisson, Laila Marie; Nemeth, Christina Linnea; Goodman, Jordan; Moser, Ann B.; Jones, Richard Owen; Fatemi, Ali; Singh, Jaspreet
Abstract: Adrenomyeloneuropathy (AMN), the slow progressive phenotype of adrenoleukodystrophy (ALD), has no clinical plasma biomarker for disease progression. This feasibility study aimed to determine whether metabolomics and micro‐RNA in blood plasma provide a potential source of biomarkers for AMN disease severity. Metabolomics and RNA‐seq were performed on AMN and healthy human blood plasma. Biomarker discovery and pathway analyses were performed using clustering, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and regression against patient's clinical Expanded Disability Status Score (EDSS). Fourteen AMN and six healthy control samples were analyzed. AMN showed strong disease‐severity‐specific metabolic and miRNA clustering signatures. Strong, significant clinical correlations were shown for 7‐alpha‐hydroxy‐3‐oxo‐4‐cholestenoate (7‐HOCA) ( r 2 = 0.83, p < 0.00001), dehydroepiandrosterone sulfate (DHEA‐S; r 2 = 0.82, p < 0.00001), hypoxanthine ( r 2 = 0.82, p < 0.00001), as well as miRNA‐432‐5p ( r 2 = 0.68, p < 0.00001). KEGG pathway comparison of mild versus severe disease identified affected downstream systems: GAREM, IGF‐1, CALCRL, SMAD2&3, glutathione peroxidase, LDH, and NOS. This feasibility study demonstrates that miRNA and metabolomics are a source of potential plasma biomarkers for disease severity in AMN, providing both a disease signature and individual markers with strong clinical correlations. Network analyses of affected systems implicate differentially altered vascular, inflammatory, and oxidative stress pathways, suggesting disease‐severity‐specific mechanisms as a function of disease severity.